(untitled) (Semiárida, 2020)
The analysis of the responses of ecosystems to environmental change is a scientific challenge because of the complexity of interrelated natural processes acting at different temporal and spatial scales. Climatic variations that occur along a transect length in the province of Neuquén are reflected in two major macro-homogeneous regions (Andean and Extra-Andean) with their respective sub-regions. These differences can manifest significant changes in the flora, vegetation and primary productivity of vegetation. The wetland “mallines” are considered key elements in Patagonian livestock production systems and the intensification of use without sustainable management has caused a considerable deterioration of the resource producing its loss. The result of the combination of climate factors, substrate, topography and vegetation defines current or real human action on the system independently of the factors that have conditioned its establishment and permanence. Knowing the floristic composition, vegetation and forage production in the meadows “mallines” distributed in the east-west longitudinal gradient Neuquén allows appropriate use of resources and maintenance of sustainable development over the years. The objective of this study was to conduct an exploration of the variability that may occur in meadows under different environmental conditions and to estimate indirectly the forage produced.